Peran Dinas Perikanan Dalam Pemberdayaan Petani Rumput Laut Di Desa Matakus Kecamatan Tanimbar Selatan Kabupaten Kepulauan Tanimbar - Meisye Fordatkosu; Hengky. V. R. Pattimukay; I. Y. Rahanra Rahanra (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This research is a qualitative descriptive study that aims to find out the role of the Fisheries Service in Empowering Seaweed Farmers in Matakus Village. This research was conducted in Matakus Village, South Tanimbar District, Tanimbar Islands Regency. Primary data collection was carried out through interviews with a number of informants who were considered to be directly involved in the Process of the Fisheries Service's Role in Empowering Seaweed Farmers in Matakus Village. The research results show (1). In providing training, the Fisheries Service focuses on determining the location, providing seeds and designing cultivation methods that really help seaweed farmers in dealing with existing problems. For example in dealing with pests. (2). Providing tools to seaweed farmers is very helpful because most of the seaweed farmers have old tools and are damaged.(3). Providing funds to seaweed farmers can assist farmers in completing cultivation infrastructure such as buying stakes, cork, main rope and also increasing the enthusiasm of seaweed farmers in cultivating existing seaweed. Based on the results of the research above, it is suggested to the Department of Fisheries to continue to conduct training for seaweed farmers to improve the ability of farmers in seaweed cultivation. It is hoped that the Fisheries Service will continue to provide tool assistance to farmers so that during the cultivation process the farmers do not lack the tools needed. It is hoped that the Fisheries Service will continue to provide funds to seaweed farmers in meeting all the needs of farmers and can increase seaweed production in Matakus Village.